2013
DOI: 10.1158/1078-0432.ccr-13-1734
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Hypomethylation of EpCAM-Regulated Bone Morphogenetic Protein Gene Family in Recurrent Endometrial Cancer

Abstract: Purpose Epigenetic regulation by promoter methylation plays a key role in tumorigenesis. Our goal was to investigate whether altered DNA methylation signatures associated with oncogenic signaling delineate biomarkers predictive of endometrial cancer recurrence. Experimental Design Methyl-CpG-capture sequencing was used for global screening of aberrant DNA methylation in our endometrial cancer cohort, followed by validation in an independent The Cancer Genome Atlas (TCGA) cohort. Bioinformatics as well as fun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 66 publications
1
34
0
Order By: Relevance
“…Supporting our previous observation that EGF treatment led to changes in an epithelial morphology to a more fibroblastic mesenchymal appearance in RL95-2 cells (16), the AFM results further provide quantitative proof of their elevated softness and reduced adhesiveness, leading to an increase in cell movement. This enhanced cell movement follows EGF stimulation in a time-dependent manner.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Supporting our previous observation that EGF treatment led to changes in an epithelial morphology to a more fibroblastic mesenchymal appearance in RL95-2 cells (16), the AFM results further provide quantitative proof of their elevated softness and reduced adhesiveness, leading to an increase in cell movement. This enhanced cell movement follows EGF stimulation in a time-dependent manner.…”
Section: Discussionsupporting
confidence: 86%
“…Images were visualized by Nikon Eclipse microscope (Nikon Instruments). Western blot analysis was performed as described previously (16). Antibodies against α-tubulin (membrane/cytoplasmic fraction) and Lamin B1 (nuclear fraction, Abcam) were used as loading controls.…”
Section: Methodsmentioning
confidence: 99%
“…65 Genome-wide analysis of DNA methylation has shown that the epigenetic process can also occur in chromosome regions such as contiguous CpG islands and gene families. [66][67][68] Hypermethylation of HOXA gene clusters was reported in breast and lung cancer. 69,70 Lastly, the protocadherin (PCDH) gene cluster was found to be hypermethylated in Wilms tumor and the region across chromosome 2q14.2 in colorectal cancer.…”
Section: Dna Methylation Dysregulation In Tumor Initiation and Develomentioning
confidence: 99%
“…We have used MBDCap-seq to study DNA methylation alterations in a large number of patients from diverse cancer types including breast 12 , endometrial 13 , prostate 14 , and liver cancers among others. Here we demonstrate some information from the breast cancer study published recently 12 .…”
Section: Representative Resultsmentioning
confidence: 99%